African and Chinese Managerial Practices: A Cross-Cultural Comparison - Abodohoui, Alexis; Su, Zhan; Bocco, Bertrand; Chrysostome, Elie (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2020)
In recent years, China has become Africa’s most important economic partner. Chinese companies of all sizes and sectors bring investments, managerial know-how and entrepreneurial energy to all 54 African countries. China also plays host to the largest population of African migrants seeking business opportunities as well as African students in search of renowned universities. It is therefore useful to compare management practices between China and Africa. Through an analytical review, our study highlights the similarities and differences of management philosophies, managerial styles, networking, and entrepreneurship. This study helps strengthen knowledge of Chinese and African management styles and suggests directions for future studies that could ensure the success of the collaboration between China and Africa.